Cellular and Clinical Analyses of Autologous Bone Marrow Aspirate Injectate for Knee Osteoarthritis: A Pilot Study. Issue 4 (13th July 2020) - Wells, Kristina; Klein, Michael; Hurwitz, Nicole; Santiago, Kristen; Cheng, Jennifer; Abutalib, Zafir; Beatty, Nicholas; Lutz, Gregory
Abstract : Introduction: Knee osteoarthritis (OA) is characterized by pain and functional deficits. Common conservative strategies include medications, physical therapy, and intra‐articular injections. Recently, treatment using autologous cell injections has increased. Objective: To characterize the cellular content of bone marrow aspirate (BMA) and to evaluate the effect of intra‐articular autologous BMA injections in patients with mild knee OA. Design: Prospective pilot observational study. Setting: Academic institution. Patients: Eleven patients with unilateral or bilateral mild knee OA (15 knees) were included in the cellular analysis. Ten patients (13 knees) were included in the overall (cellular and clinical) analysis. Interventions: BMA was aspirated from patients' iliac crests and then injected intra‐articularly under fluoroscopic and/or ultrasound guidance. BMA samples were analyzed using flow cytometry, colony forming unit (CFU) assays, and enzyme‐linked immunosorbent assays. Questionnaires assessing pain and function were administered preinjection and at 1, 3, 6, and 12 months postinjection. Side effects and satisfaction were assessed. Main Outcome Measures: Total nucleated cell (TNC) concentration, mesenchymal stem cell (MSC) concentration, CFU count, and interleukin‐1 receptor antagonist (IL‐1Ra) concentration. Results: BMA sample analyses revealed wide ranges in TNC concentration (173300‐4 491 050 cells/mL), MSC concentration (0‐500 cells/mL), CFUs (0‐19), and IL‐1Ra concentration (2806‐29 394 pg/mL). Improvements in Knee Injury and Osteoarthritis Outcomes Score for Joint Replacement were observed throughout the 12‐month follow‐up period (F[4, 12] = 12.29, P  < .001). Additionally, current, usual, best, and worst numerical rating scale pain scores significantly decreased over time ( P  < .001). Patient satisfaction was high (range: 8.1 ± 2.1‐8.8 ± 1.9), and side effects were uncommon. Conclusions: The cellular content of BMA samples varied widely between patients and was lower than the anticipated yield reported by the device's manufacturer. However, intra‐articular BMA injections for knee OA in a small pilot cohort appeared to be safe with potential therapeutic value. Larger, prospective, double‐blinded studies are warranted.